State and federal policies and school meal participation: A descriptive analysis from Arizona - Shreya Raval; Sarah Martinelli; Tatum Dykstra; Francesco Acciai; Juliana Cohen; Francesco Ramponi; Punam Ohri-Vachaspati (PLoS ONE, 2026)
Starting in 2023, the state of Arizona implemented a series of policies to improve access to school meals: (1) A state policy to eliminate co-pays for reduced-price meals, implemented in January, 2023; (2) the federal Medicaid Direct Certification demonstration project, implemented in August, 2023; and (3) a federal policy to expand eligibility for Community Eligibility Provision (CEP), implemented in October, 2023. We track changes in school meal participation rates and number of meals served for breakfast and lunch after implementation of these policies using longitudinal data from 1,730 public and charter schools in Arizona. Outcomes were compared across different policy periods with baseline- the period prior to implementation of the three policies. Following the co-pay policy elimination, compared to baseline, participation among students eligible for reduced-price category increased significantly by about 10%, for both breakfast and lunch. After the implementation of all three policies, compared to baseline, student participation across all eligibility categories increased by 4.8% and 7.2% for breakfast and lunch, respectively. Similarly, compared to baseline, with all three policies in place, the average number of free meals served daily increased by 27.9% and 26.8% for breakfast and lunch, respectively. School CEP participation expanded from 451 to 737 schools- a 63% increase following the implementation of the lower eligibility threshold for CEP participation. As a result of increased school CEP participation, an additional 147,125 children had access to free school meals. Participation trends across eligibility categories varied by school urbanicity, grade level, and demographic characteristics of enrolled students. These findings suggest that implementing state and federal policies can enhance access to and participation in school meal programs.